Qasr Mushash-Survey, Jordanien: Die Arbeiten der Jahre 2014 - Bartl, Karin (e-Forschungsberichte des DAI, 2023)
The early Islamic site of Qasr Mushash east of Amman is characterized by a variety of different types of architectural units such as representative, domestic and hydraulic structures, distributed over two widely separated areas of settlement. The investigations are focused on the preparation of the topographical plan of the site and the complete documentation of the individual structures. The data generated so far form the basis for the definition of the function of the site which might have been used as a caravan halt as well as a temporary residence for elites.